Serum syndecan-1 concentration in hemolysis, elevated liver enzymes, and low platelets syndrome: A case report - Nishio, Ayane; Kamidani, Ryo; Okada, Hideshi; Suzuki, Keiko; Suzuki, Kodai; Miyake, Takahito; Okamoto, Haruka; Doi, Tomoaki; Suzuki, Akio; Yoshida, Shozo; Ogura, Shinji (Frontiers in Medicine, 2023)
Background Hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome occurs in pregnant and postpartum individuals. We observed serum syndecan-1 (SDC-1) levels, which is a component of the glycocalyx, in a patient with HELLP syndrome from admission to the postpartum period and examined their association as reflecting the pathophysiology related to endothelial injury. Case presentation A 31-year-old primiparous female patient without a previous medical history at a gestational age of 37 weeks and 6 days was transferred to our hospital the morning after a visit to a previous hospital with headache and nausea. Elevated transaminase, platelet count, and proteinuria were noted. Head magnetic resonance imaging revealed a caudate nucleus hemorrhage and posterior reversible encephalopathy syndrome. After she delivered her newborn through an emergency cesarean section, she was admitted to the intensive care unit. On day 4 post-delivery, the patient’s D-dimer concentration was elevated, and contrast-enhanced computed tomography was performed. The results indicated pulmonary embolism, and heparin administration was initiated. The serum SDC-1 level was highest on day 1 post-delivery and quickly decreased subsequently; however, it remained elevated during the postpartum period. Her condition gradually improved, and she was extubated on day 6 and discharged from the ICU on day 7 post-delivery. Conclusion We measured SDC-1 concentration in a patient with HELLP syndrome and found that the clinical course correlated with SDC-1 levels, indicating that SDC-1 is elevated immediately before and after pregnancy termination in patients with HELLP syndrome. Therefore, SDC-1 fluctuations, combined with the elevation of the D-dimer level, may be a potential marker for the early detection of HELLP syndrome and estimation of the syndrome’s severity in the future.